Regioselective installation of fluorosulfate (–OSO2F) functionality into aromatic C(sp2)–H bonds for the construction of para-amino-arylfluorosulfates. Issue 44 (14th May 2019) - Fang, Wan-Yin; Zha, Gao-Feng; Zhao, Chuang; Qin, Hua-Li
Abstract : The synthesis of novel para -amino-arylfluorosulfates was achieved through installing fluorosulfate functionality into aromatic C(sp 2 )–H bonds mediated by sulfuryl fluoride. Abstract : The construction of para -amino-arylfluorosulfates was achieved through installation of fluorosulfate (–OSO2 F) functionality into aromatic C(sp 2 )–H bonds by the reaction of N -arylhydroxylamine with sulfuryl fluoride (SO2 F2 ). This method provides a mild process for the preparation of broadly applicable fluorosulfate moieties without the requirement of phenols or transition metals.